Nivel de conocimiento y aplicación de medidas de bioseguridad en estudiantes del VIII - IX ciclo de obstetricia UNSM - T en el hospital II-2 Tarapoto. Junio - Setiembre 2012 - Sangama Del Aguila, Luligandy (2012)
This study aimed to determine the level of knowledge and application of biosecurity measures, students in VIII - IX cycle, career of obstetrics at UNSM - T in the Hospital II - 2 Tarapoto June - September 2012. We performed crosssectional descriptive study. The sample consisted of 43 students, which met the inclusion and exclusion criteria. To measure the variable level of knowledge, was used as the survey method and applied a checklist to assess the implementation of biosecurity measures. The results were: The knowledge level of biosecurity measures conceptualization was located in low with 53.5% and 46.5%. Conceptualized as high; in relation to the level of knowledge about some biosecurity barriers are high, regarding the use of gloves, use of mask and use mandolins; in regard to the level of knowledge of contaminated medical waste management is low with 60w.5%; In the level of general knowledge about biosecurity measures is high with a 51.16% and with respect to the variable application, reported higher percentages than ever students use biosecurity measures percentages and not very favorable and always use it sometimes